Improvement on fuel characteristics of biomass and refused derived fuel with torrefaction - Azpilicueta, Ander (2022)
The search for sustainable energy alternatives has been increasingly important, not only because the depletion of fossil fuels, but also due to the necessary reduction in the emission of greenhouse gases. The use of renewable energy has contributed to the mitigation of this problem, but this doesn’t always adapt to the requirements of energy demand. The energy of biomass, in particular by the combustion of vegetal biomass, is a form already in use and with broad application, from domestic heating equipment to thermoelectric power plants. An alternative energy source is the refuse derived fuels, RDF, which offer a double benefit, given they provide an energy resource and avoid the occupation of landfill space. However, the use of biomass or RDF has limitations, due to the fuel quality. As received, it presents low heating value, low adiabatic flame temperature and low density. The improvement of the properties of these fuels may be obtained by torrefaction. This is a low-temperature pyrolysis process, where the heating gradient, top temperature and process duration must be controlled. In this study, an experimental prototype was developed for torrefaction trials. During the torrefaction experiments the heating rate and maximum temperature were controlled, and were measured sample temperatures, mass decay and also the composition of the gases released. Later, the higher heating value, density and hydrophilicity of biomass and RDF samples, as received and with various stages of torrefaction, were measured, confirming the advantage of applying this thermal process in the improvement of the biomass and RDF fuel properties.